Analisis Hasil Uji Sondir pada Rumah Rusun Pejambon Tipe 45 8 Lt Untuk Mengetahui Daya Dukung dan Penurunan Pondasi Tiang Pancang - Mauliyatul Hasanah; Pungky Dharma Saputra (Institut Teknologi Garut, 2024)
Gambir sub-district is one of the sub-districts in Central Jakarta. Central Jakarta is also a big and busy city in Indonesia. The construction of an 8-storey type 45 flat in Pejambon, Central Jakarta was carried out because many soldiers of the Indonesian National Army served in Jakarta, so they needed a flat. The first step in the construction of type 45 8-storey flats is to conduct soil investigations with the help of sondir test equipment, from the soil chart, a soft soil type is obtained. The sondir results with a depth of 6.6 m obtained hard soil with a qc value> 250 kg f / cm2. This type 45 8-storey flat is carried out a soil investigation so that the parameters to be analyzed are the bearing capacity of the soil and the foundation settlement, the decrease in the Single pole is 0.004 and the allowable is 0.04 which is the value of the decrease in the Single pole is smaller than the allowable value, so that the foundation plan can be carried out according to the purpose of the building. The foundation must be installed first before other elements are formed.